Influence of Organic Matter on Soil Aggregation and Erodibility of Some Malaysian Soils - Adan, Tajuddin (1992)
The dominant role of organic matter in promoting aggregate stability and the strong relation ship between the latter and soil erodibility are observed consistently by many researchers . These findings suggest that, organic matter and soil erodibiIity should have a strong relation ship too. However, this is not always true. Some workers found a weak relationship between the two. with this background,experiments were conducted to examine the role of organic matter and its constituents on soil aggregation and erodibility for some Malaysian soils.